Dogmatikk som samtidsteologi - Eikrem, Asle (Dansk Teologisk Tidsskrift, 2011)
The article develops a sketch for a critical systematic reconstruction of Niels Henrik Gregersen’s framework for “Dogmatics as Contemporary Theology”. Three main issues are taken up for discussion. First, the relation between semantics and pragmatics is investigated. Secondly, the important theoretical procedure of “explication” is clarified in accordance with the three orders of systematic theological procedures found in Gregersen’s framework. Through this discussion a third, and final, problem announces itself: how are we to determine the thematic fields of each order of systematic theological discourse: theology1, 2, and 3? From the soil tossed and turned by this discussion, and contrary to strong trends in many so-called post-metaphysical ways of thinking, reasons are given why an explicated depth-metaphysical framework is necessary for clarifying the procedures of ”Dogmatics as Contemporary Theology”.